(untitled) (Bangladesh Journal of Urology, 2025)
Malacoplakia is a very rare chronic granulomatous disease. It can affect almost all organs of the urogenital system, among which the urinary bladder is most common. During cystoscopy, it may reveal sessile mass which may cause misdiagnosis as malignancy. Therefore, only histopathological examination can differentiate it from malignancy. We reported a case of a 31 years old male presented with generalised weakness, low grade fever, dysuria, frequency and urgency but no pyuria or haematuria. Diagnostic urethrocystoscopy was performed which revealed multiple sessile mass obscuring left ureteric orifice, but right ureteric orifice was identified properly and right sided URS was done & soft plaque like lesion was found at distal ureter from which biopsy was taken. Then TUR of bladder mass was done resulting visualization of left ureteric orifice, followed by left sided URS in which whole of the left ureter was found dilated upto renal pelvis with no mass lesion. Microscopic examination of tissue taken by both transurethral resection and URS biopsy revealed features of malacoplakia. Postoperatively, the patient was treated with broad spectrum antibiotics and other supportive measures to prevent further deterioration of renal function. Ultimately, the patient recovers well with no more progression to obstructive nephropathy. Urologists should emphasize multifocal malacoplakia involving more than one genitourinary organ presenting with obstructive nephropathy. Early diagnosis and treatment with long term oral antimicrobial agents combined with cholinergic drugs or vitamin C, as well as full surgical excision (i.e. transurethral resection) should be done to obtain better therapeutic effect against malacoplakia. Bangladesh J. Urol. 2025; 28(1): 44-48